Implementasi Metode Dempster-Shafer untuk Mendiagnosis Jenis Tumor Jinak pada Manusia - Moch. Maulana Alrizzaqi; Rekyan Regasari Mardi Putri; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Tumor is one type of cell that grows by the speed of irregular and not having a useful function for the human body. A tumor can be categorized into two types of a malignant tumor (cancer) and a benign tumor.Benign tumor different from a malignant tumor that may lead to death by those with, some cases benign tumor that growing on certain vital parts that indirectly can disrupt vital organs, a lack of knowledge to knowing kind of benign tumor often makes hard to perform the act of treating a tumor suffered due to a kind of benign tumor of which various by symptoms and the characteristics of that is almost the same, also required special knowledge to recognize and how to deal with the tumor with To research this problems are addressed by making a system with an implement a method of dempster-shafer aimed at to diagnose the types of benign tumor suffered by man , hopefully this system is expected to help users in diagnosing kinds of tumors benign. After doing some test the result ended on 80% accuraccy points, thats mean that this systems are able to help user to detect the kind of benign tumor